Practical Handbook for Small-Gauge Vitrectomy A Step-By-Step Introduction to Surgical Techniques - Spandau, Ulrich; Heimann, Heinrich (Springer Berlin Heidelberg : Imprint: Springer, 2012)
Since the development of 23G vitrectomy in 2004, the technique has revolutionized retinal surgery by overcoming a number of the problems associated with 20G and 25G systems and offering significant improvements in surgical capability and fluidics. This important book first discusses the instruments and equipment employed in 23G vitrectomy and then explains, step by step, the various surgical techniques with the aid of informative diagrams and many high-quality photos. In addition, videos are included that document the different procedures, from the straightforward to the demanding. This book will serve as an immensely useful guide for all surgeons who are intending to make use of this exciting and increasingly used technique.